2011
DOI: 10.1002/ajh.21911
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early‐onset and late‐onset post‐transplant lymphoproliferative disorder in kidney recipients in the United States

Abstract: Summary Incidence of post-transplant lymphoproliferative disorder (PTLD) is bimodal, suggesting distinct early-onset and late-onset subtypes. We evaluated differences in risk factors for early-onset and late-onset PTLD in a retrospective cohort study of U.S. kidney transplant recipients using data from the Scientific Registry of Transplant Recipients (N=156,740, 1999–2007). Multivariate hazard ratios (HRs) for risk factors were estimated using proportional hazards models. For early-onset PTLD, significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
150
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(185 citation statements)
references
References 27 publications
21
150
2
4
Order By: Relevance
“…(Nee et al, 2011) Quinlan et al found that non-Hispanic whites were at significantly higher risk of early-onset and late-onset PTLD than other racial or ethnic groups. (Quinlan et al, 2011) In the same study it was also demonstrated that CMVseronegativity was associated with increased early-onset PTLD risk. (Quinlan et al, 2011) However, it seems that the role of CMV and HCV as risk factors for PTLD is controversial, as is that of herpes simplex or simian virus infections.…”
Section: Other Risksmentioning
confidence: 76%
See 2 more Smart Citations
“…(Nee et al, 2011) Quinlan et al found that non-Hispanic whites were at significantly higher risk of early-onset and late-onset PTLD than other racial or ethnic groups. (Quinlan et al, 2011) In the same study it was also demonstrated that CMVseronegativity was associated with increased early-onset PTLD risk. (Quinlan et al, 2011) However, it seems that the role of CMV and HCV as risk factors for PTLD is controversial, as is that of herpes simplex or simian virus infections.…”
Section: Other Risksmentioning
confidence: 76%
“…(Caillard et al, 2005;van Leeuwen et al, 2009) This difference may be related to different eras of treatment and increasing experience with antibody-based induction therapies, leading to an attenuation of associated PTLD risks. (Quinlan et al, 2011) In contrast, PTLD occurred 2 to 3-fold more frequently after receipt of OKT3 than with other drugs. (Opelz & Dohler, 2004;Taylor et al, 2005) Gajarski et al report that as induction agents thymoglobulin and IL-2R antagonists had the lowest associated PTLD rates compared to OKT3, attributing this to its long-lasting depletional effects on CD-3 positive Tlymphocytes.…”
Section: Immunosuppressionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study young, Caucasian and EBV mismatched children were more likely and African-American children were less likely to develop PVL. These demographic and clinical characteristics have been identified as risk factors for PTLD in the previous studies; however, these characteristics have not been previously assessed for development of EB PVL [1,[8][9][10]. Concern has been raised that thymoglobulin may play a role in the development of PTLD as it has been shown to deplete poly functional T cells in HIV infected kidney transplant recipients and activate EBV replication [11].…”
Section: Discussionmentioning
confidence: 99%
“…Trasplante multivisceral > intestino > pulmón > corazón/pulmón > corazón > riñón Presencia de malignidades pretrasplante La incidencia de ELPT tiene una distribución bimodal, con un pico temprano (primeros dos años postrasplante), y uno tardío, con diferencias en los factores de riesgo y los hallazgos histológicos, lo que sugiere mecanismos diferentes para su producción. Los casos tempranos parecen ser mediados principalmente por la infección con VEB en el contexto de la inmunosupresión profunda, y los tardíos se relacionan con la inmunosupresión prolongada, la edad avanzada y probablemente la exposición a agentes específicos, lo cual se ha evidenciado en diferentes estudios (5)(6)(7)(8).…”
Section: Incidencia Y Factores De Riesgounclassified